1961
DOI: 10.1037/h0040901
|View full text |Cite
|
Sign up to set email alerts
|

Interrelationships among measures of field dependence, ability, and personality traits.

Abstract: The background review, the study, and its discussion are concerned with males only. It is clear from the results of Witkin, Lewis, Hertzman, Machover, Meissner, and Wapner (1954) and Bieri, Bradburn, and Galinski (19S8), that the introduction of sex as a variable in perception-personality relationships leads to a large and bewildering number of interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
32
0

Year Published

1963
1963
2007
2007

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(35 citation statements)
references
References 22 publications
3
32
0
Order By: Relevance
“…Finally, as an incidental result of a study focused on personality correlates of field dependence, Elliott (48) reported that field dependent subjects [identified by Witkins' (136) procedures] described themselves on a semantic differential scale and on a modification of Barron's (11) Independence of Judgment Scale in "conventional and socially desirable terms." Several studies have been reported which have focused, at least in part, on attempts to define the construct, "social desirability," to measure its stability, or to investigate relationships among various measures of it.…”
Section: Christie and Lindauermentioning
confidence: 98%
“…Finally, as an incidental result of a study focused on personality correlates of field dependence, Elliott (48) reported that field dependent subjects [identified by Witkins' (136) procedures] described themselves on a semantic differential scale and on a modification of Barron's (11) Independence of Judgment Scale in "conventional and socially desirable terms." Several studies have been reported which have focused, at least in part, on attempts to define the construct, "social desirability," to measure its stability, or to investigate relationships among various measures of it.…”
Section: Christie and Lindauermentioning
confidence: 98%
“…12,21 Thus, FD are more liable to answer according to social expectations. 22 Similarly, the belief in paranormal phenomena is more common amongst FD. 23 Field-dependency had been linked also to cultural differences as cross-cultural studies found that Westerners are relatively more FI than East Asians, [24][25][26][27] a finding that correlates well with the strong emphasis in Western culture on individualism, where the self is experienced as an autonomous, independent entity, as opposed to East Asian cultures' emphasis on collectivism, where the self is perceived as fundamentally interconnected and in relationships with important others.…”
Section: Field Dependencymentioning
confidence: 99%
“…No causal relations can be inferred in this kind of work until we can be more sure about accuracy of measurement. Elliot (1961) has remarked that "field dependence . .…”
Section: ( 4 ) E F F E C T Of Instractionsmentioning
confidence: 97%